Psichosocial intervention in early radicalization approach with scrum methodology - Rodríguez-Rodríguez, Juan Carlos; Rodríguez-Góngora, Josefina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The main objective of this manuscript is to present a new methodology for addressing violent radicalization using the Scrum methodology, widely used in software construction environments, as the main tool. A work methodology focused on the recipients of the intervention is proposed. The Scrum method has been shown, on many occasions, to be very effective as a collaborative learning strategy, having been used in university environments for the development of high-quality projects for short periods of time. Addressing the charter of values and intervening towards values incompatible with violence will reduce radicalization in adolescents.